Resilience and Transformation in the Cruise Industry: Navigating Post-Pandemic Recovery and Sustainable Futures - Ryan, Michael Anthony (Digital Repository of Theses, 2024)
This study takes a mixed methods approach to resilience in a time of crisis for the cruise industry. The industry dealt with unprecedented hardships presented by COVID-19. It looks at what strategic adjustments were made in light of the hardships. There were disruptions and health concerns. This research shows how agility can be incorporated in times of such hardships. It implemented safety protocols and redefined passenger experiences. Significant operational changes brought about improvements in sustainability. Furthermore, this research examines the crisis management strategies adopted by the cruise industry. It highlights plans incorporating health screening processes, rapid response mechanisms, and clear communication protocols. These measures addressed health concerns and laid a foundation for future crisis management frameworks. An essential finding of this study indicates that sustainability has become a focus of the cruise industry. This focus is evident through initiatives such as adopting waste recycling systems, sourcing food options, and implementing eco-friendly practices. These efforts demonstrate an increasing commitment to stewardship within the industry. The study also looks at how the cruise industry relates to the local communities it impacts. It highlights initiatives that focus on tourism and sustainability in a community-oriented approach. Combining these findings shows how the cruise industry has adapted and persevered throughout the COVID-19 pandemic. It shows how the industry has redirected its focus toward safety, sustainability, and community engagement in the post-pandemic era. It is a truly transformative process.